The Relationship Between The Percentage of Solar Radiation Under The Shade of Stand and The Growth of Cardamom - Indriyanto Indriyanto (JURNAL SAINS NATURAL, 2023)
Cardamom can live under the shade of stand, but require adequate shade for optimum growth. Therefore, this research aims to determine the relationship between the percentage of solar radiation under the shade of stand on the growth of cardamom, and to estimate the percentage of solar radiation that affects the optimum growth of cardamom. The research was conducted in 5 farmer-cultivated areas planted with cardamom in Tahura Wan Abdul Rachman. In each farmer's arable area, 3 plots of 5 m x 5 m were made, which were placed randomly to observe the growth of cardamom. The data collected includes: growth of cardamom, tree species that make up forest garden stands, solar radiation under the shade or in the open, air temperature, and humidity. The data were analyzed by quadratic regression at the 5% significance level. The results showed that the difference in the shade of stands had a significant effect on the growth of cardamom. All cardamom growth variables were significantly correlated with the percentage of solar radiation under the shade of stand. The optimal number of stems is 49.5 stems at a percentage of 63% solar radiation. The optimal plant height of 146.74 cm at a percentage of 67% solar radiation. The optimal number of leaves per clump is 235.296 leaves at 60% solar radiation percentage. The number of flower bunches per cluster is optimal as much as 23.4 bunches at the percentage of solar radiation 60.5 %. The optimal number of fruits per fruit bunch is 8.7 fruits at the percentage of solar radiation 56 %. Thus, cardamom plants will grow optimally under the shade of the standing canopy with a percentage of solar radiation from 56% to 67%.Keywords:  cardamom;  forest gardens;  growth;  shade; standABSTRAKHubungan Persentase Radiasi Matahari di Bawah Naungan Tajuk Tegakan dengan Pertumbuhan KapulagaKapulaga dapat hidup di bawah naungan tegakan, akan tetapi membutuhkan naungan yang memadai untuk pertumbuhan optimal.  Oleh karena itu, penelitian bertujuan untuk mengetahui hubungan persentase radiasi matahari di bawah naungan tegakan kebun hutan dengan pertumbuhan kapulaga, serta mengestimasi persentase radiasi matahari yang berpengaruh terhadap pertumbuhan optimum kapulaga. Penelitian dilakukan di 5 areal garapan petani yang ditanami kapulaga dalam Tahura Wan Abdul Rachman. Data yang dihimpun meliputi: pertumbuhan kapulaga,  jenis pohon penyusun tegakan kebun hutan, radiasi matahari di bawah naungan maupun di tempat terbuka, temperatur udara, dan kelembapan udara. Data dianalisis regresi kuadratik pada taraf nyata 5%. Hasil penelitian menunjukkan bahwa perbedaan naungan tegakan kebun hutan berpengaruh nyata terhadap pertumbuhan kapulaga. Semua variabel pertumbuhan kapulaga berhubungan nyata secara kuadratik dengan persentase radiasi matahari di bawah naungan tegakan. Jumlah batang per rumpun yang optimal sebanyak 49,5 pada persentase radiasi matahari 63%. Tinggi kapulaga yang optimal 146,74 cm pada persentase radiasi matahari 67%. Jumlah daun per rumpun yang optimal sebanyak 235,296 helai pada persentase radiasi matahari 60%. Jumlah tandan bunga per rumpun yang optimal sebanyak 23,4 pada persentase radiasi matahari 60,5%. Jumlah buah per tandan yang optimal sebanyak 8,7 pada persentase radiasi matahari 56%. Dengan demikian, kapulaga akan tumbuh secara optimal di bawah naungan tegakan yang persentase radiasi matahari sebesar 56% hingga 67%.Kata kunci: kapulaga; kebun hutan; naungan; pertumbuhan; tegakan